Turning on Light Emission of a Dark Pro‐Aggregation‐Induced Emission Luminogen in Aqueous Media Through Reductase‐Modulated Derotation. Issue 4 (8th February 2021) - Xu, Changhuo; Zou, Hang; Zhao, Zheng; Zheng, Zheng; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Sung, Herman H. Y.; Williams, Ian D; Chen, Sijie; Zheng, Lei; Tang, Ben Zhong
Abstract : The development of dark pro‐aggregation‐induced‐emission luminogens (pro‐AIEgens) based on the solid‐state intramolecular motion–caused quenching effect has been rarely reported in biochemical analysis. Herein, an azo‐conjugated pro‐AIEgen derived from tetraphenylethene is constructed. Due to the active molecular motion of the azo bond, it retains a nonemissive property in both solution and solid forms. The obtained pro‐AIEgen can be internalized by living cells and undergo reductase‐modulated derotation under hypoxia to emit light. It shows increasing fluorescence when the intracellular oxygen concentration becomes lower, making it a potential probe to sense the hypoxic environment. The present probe can also visualize the hypoxic environment created by photodynamic therapy treatment. Abstract : By equipping an aggregation‐induced emission luminogen (AIEgen) with a photoactive azo group, a new strategy to design and synthesize dark pro‐AIEgens is proposed for intracellular reductase imaging. The emission of the obtained pro‐AIEgen is dormant in both solution and solid states and can be awakened to report the hypoxic level in living cells upon reductase‐mediated derotation.